New species and new geographical record of Ochrotrichia Mosely 1934 Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil - Cavalcante, Bruna Maria Silva; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2018)
Ochrotrichia, with about 160 extant species in the New World, is the most diverse genus assigned to the Ochrotrichiinae. Despite its diversity, only eight species were previously recorded from Brazil, only one from Rio de Janeiro state. In this paper, we describe three new species from Parque Nacional da Tijuca, an Atlantic Forest area at Rio de Janeiro. Ochrotrichia nematomorpha sp. nov. is placed within the O. xena Group, having a plate-like tergum X, with an unusual phallus which is slender and pointed apically. Ochrotrichia sagitta sp. nov. and O. taunay sp. nov. belong to the O. aldama Group, each having a divided tergum X, but being distinguished from the others in this group by the arrowhead-like apex of left lateral process of tergum X (O. sagitta) and the presence of two dorsal spine-like projections on tergum X (O. taunay). Furthermore, O. caatinga Souza, Santos & Takiya, 2014 is reported for the first time from Rio de Janeiro state.